2016
DOI: 10.5539/ells.v6n1p47
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Learning Strategies Employed by Undergraduate EFL Jordanian Students

Abstract: The present study investigates the various vocabulary learning strategies (VLSs) used by undergraduate Jordanian students majoring English Language and Literature in Jordanian universities. The five categories of the vocabulary learning strategies (Memory, Determination, Social, Cognitive, and Metacognitive) were used in this study following Schmitt's taxonomy. For this purpose, a questionnaire containing forty items selected from Schmitt's (1997) Vocabulary Learning Strategies Questionnaire (VLSQ) was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 22 publications
3
18
0
1
Order By: Relevance
“…Table 3 shows that three discovery strategies registered high frequency use by respondents and they range from 80.0% to 85.0%. These are the strategies of (a) using contextual guessing (80.0%), (b) asking classmates about the meaning of new words (85.0%), and (c) using English-Arabic dictionaries (88.3%).This finding is in line with Schmitt's (1997), Al-Fuhaid's (2004) and Rabadi's (2016) studies, which reported that using bilingual dictionary strategy was the most frequently used by respondents. In addition, this finding is consistent with Schmitt's (1997), Fan's (2003), Al-Fuhaid's (2004), Kulikova's (2015) and Hashemi and Hadavi's (2015) studies, in which, guessing strategy was the most frequently used by their respondents.…”
Section: Findings On Discovery Strategiessupporting
confidence: 76%
“…Table 3 shows that three discovery strategies registered high frequency use by respondents and they range from 80.0% to 85.0%. These are the strategies of (a) using contextual guessing (80.0%), (b) asking classmates about the meaning of new words (85.0%), and (c) using English-Arabic dictionaries (88.3%).This finding is in line with Schmitt's (1997), Al-Fuhaid's (2004) and Rabadi's (2016) studies, which reported that using bilingual dictionary strategy was the most frequently used by respondents. In addition, this finding is consistent with Schmitt's (1997), Fan's (2003), Al-Fuhaid's (2004), Kulikova's (2015) and Hashemi and Hadavi's (2015) studies, in which, guessing strategy was the most frequently used by their respondents.…”
Section: Findings On Discovery Strategiessupporting
confidence: 76%
“…Finally, metacognitive strategy is a conscious process whereby the learner is able to make a decision to plan, monitor and evaluate the learning process using methodologies that support the learner to understand the way he or she best learns. In this strategy, the learners employ self-awareness and are able to "learn to think," as well as "think to learn" to control and evaluate their learning (Lai, 2016;Rabadi, 2016;Baskin et al, 2017).…”
Section: The Importance Of Vls In Language Learningmentioning
confidence: 99%
“…In her study, Rabadi (2016) investigated the various vocabulary learning strategies used by undergraduate Jordanian students majoring in English language and literature in Jordanian Universities. Again, the prevalent instrument of study was Schmitt's taxonomy (1997), which covered the five categories of strategies used (memory, determination, social, cognitive, and metacognitive).…”
Section: Literature Review Of Vls In the Context Of Eflmentioning
confidence: 99%
“…Studies on the importance of learning vocabulary have been conducted over the last few decades (Halliwell, 1992;Cameron, 2001;Lessard-Clouston, 2013;Rabadi, 2016). Regarding using games to learn vocabulary, Azriel et al (2005) stated that "regardless of age or economic, ethnic, or social background, people understand the language of play".…”
Section: Slice Of Pizzamentioning
confidence: 99%